ГДЗ по алгебре 9 класс Ю.М. Колягин задание / 592

показать содержание

592 1) (х + 2)/(x-2 ) - х (х - 4) /(x^2 – 4) = (х – 2)/(x+2) – 4(3+x)/(4-x^2) 2)1+ 2/(x-1) – 6/(x^2-1) = 3/(x+1); 3) 6/(4x^2 -1) + 3/(2x+1)= 2/(2x-1) +1 4) (x+1)/(x-2) – (x+1)/(x-1)= 4/(x-1)(x-2) – (x-1)/(x-2)

учебник / задание / 592
592 
1) (х + 2)/(x-2 ) - х (х - 4) /(x^2 – 4) = (х – 2)/(x+2) – 4(3+x)/(4-x^2)
2)1+ 2/(x-1) – 6/(x^2-1) = 3/(x+1);
3) 6/(4x^2 -1) + 3/(2x+1)= 2/(2x-1) +1
4) (x+1)/(x-2) – (x+1)/(x-1)= 4/(x-1)(x-2) – (x-1)/(x-2)
решебник / задание / 592
592 
1) (х + 2)/(x-2 ) - х (х - 4) /(x^2 – 4) = (х – 2)/(x+2) – 4(3+x)/(4-x^2)
2)1+ 2/(x-1) – 6/(x^2-1) = 3/(x+1);
3) 6/(4x^2 -1) + 3/(2x+1)= 2/(2x-1) +1
4) (x+1)/(x-2) – (x+1)/(x-1)= 4/(x-1)(x-2) – (x-1)/(x-2) 592 
1) (х + 2)/(x-2 ) - х (х - 4) /(x^2 – 4) = (х – 2)/(x+2) – 4(3+x)/(4-x^2)
2)1+ 2/(x-1) – 6/(x^2-1) = 3/(x+1);
3) 6/(4x^2 -1) + 3/(2x+1)= 2/(2x-1) +1
4) (x+1)/(x-2) – (x+1)/(x-1)= 4/(x-1)(x-2) – (x-1)/(x-2)